Pengaruh BI-7 Day Reverse Repo Rate Dan Inflasi Terhadap Pembiayaan Akad Murabahah Pada Bank Umum Syariah (Periode 2018-2021) - Nilam Cahya; Isro’iyatul Mubarokah (Jurnal Ilmiah Wahana Pendidikan, 2023)
According to the phenomena that occurred, namely the decrease in interest rates and inflation during the COVID-19 pandemic in Indonesia, this study aims to determine the effect of BI-7DRR and inflation on murabahah financing. The method used is a quantitative method with secondary data obtained from monthly reports on the financial reports of Islamic banks registered with the Financial Services Authority, statistical reports on Islamic banking, the website of Bank Indonesia, and the Central Bureau of Statistics for the 2018–2021 period. The sampling technique uses a saturated sample technique, and 12 commercial samples are obtained. Data analysts use multiple linear regression analysis techniques. The results of the study prove that in the F test, simultaneously, the variables BI7DRR and inflation have a positive and significant effect on murabahah financing. Meanwhile, the individual t-test illustrates that the interest rate, or BI-7DRR, has a significant negative effect on murabahah financing and inflation has a significant positive effect on murabahah financing.